2021
DOI: 10.3390/ijerph182413326
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Differences in Compulsory Courses Offering Medicine Humanization and Medical Communication in Polish Medical Schools: Content Analysis of Secondary Data

Abstract: Medical humanity is an essential element of medical education, and the respective courses are introduced to the curricula of medical schools worldwide. However, significant differences in this type of medical education were identified in Italy, Spain, and the UK. In Poland, this issue was not yet analyzed. The classes offered on a compulsory and not elective basis secure the uniform skills of future physicians. Therefore, we were prompted to ask a question: do Polish medical students receive equal compulsory e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 46 publications
(51 reference statements)
0
8
0
1
Order By: Relevance
“…The format issue of the MH courses (elective versus compulsory) was addressed in a recent study, which identified medical students' preference for elective classes [25], agreeing with our present findings. In addition, previously, we identified vast differences between Polish universities in the form of MH classes and the time investment that varied from as much as 216 h of training to as little as 15 h during the entire course of study [19].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The format issue of the MH courses (elective versus compulsory) was addressed in a recent study, which identified medical students' preference for elective classes [25], agreeing with our present findings. In addition, previously, we identified vast differences between Polish universities in the form of MH classes and the time investment that varied from as much as 216 h of training to as little as 15 h during the entire course of study [19].…”
Section: Discussionmentioning
confidence: 90%
“…However, Polish medical universities implement MH in a wide variety of ways. At the same time, no universal curriculum model for MH classes exists [19].…”
Section: Introductionmentioning
confidence: 99%
“…W Polsce realizacja przedmiotów odnoszących się do idei humanizmu na kierunkach lekarskich jest zróżnicowana. Liczba przedmiotów związanych z medycyną humanistycz ną na polskich uczelniach wahała się od 1 do 6, natomiast całkowity wymiar nauczania wahał się od 15 do 216 godzin w zakresie zajęć obowiązkowych [41]. Ponadto przeprowa dzona w 2020 roku identyfikacja umiejętności ważnych dla przyszłych lekarzy pod kątem wykonywaniu zawodu wyka zała, że respondenci czuli się dobrze przygotowani w zakre sie kompetencji teoretycznych do wykonywania przyszłego zawodu, natomiast swoje przygotowanie praktyczne ocenili jako znacznie niższe.…”
Section: Dyskusjaunclassified
“…There are 21 universities in Poland that offer undergraduate courses in Medicine. All of these educational institutions teach a 12-term (6-year) Medicine course that ends with an MSc in Medicine [ 15 ]. The subjects taught during the first six terms (three years) are mainly theoretical, while clinical subjects are taught from the fourth year until the sixth year of the course.…”
Section: Introductionmentioning
confidence: 99%